ผลของการกระทำที่สอดคล้อง ไม่สอดคล้อง และไม่เกี่ยวข้องกับบทและระยะเวลาในการเก็บจำ ต่อความจำเหตุการณ์ที่มีบทเป็นพื้นฐานของเด็กอายุ 6-8 ปี - ณัฏฐารีย์ ศิริวิวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To examine the effects of age, script, and retention intervals; and the interaction among age, script, and retention intervals on script-based event memory of 6-to 8-year-old children. School script was used in this study. Participants were 90 primary school students. Each student was tested his/her memory twice, immediately and after 24-hour delay. The results are as follows; 1. There were no interactions of script, retention interval, and age in true and false memory. And there were no main effects of age in both true and false memory. 2. Correct recognition on atypical and irrelevant actions was significantly higher than correct recognition on typical actions (p < .001). 3. In true memory, all actions were significantly better recognized in immediate testing than delayed testing (p < .001). 4. Typical action was more significantly and falsely recognized than atypical and irrelevant actions (p < .001). 5. In false memory, all actions were significantly and poorly recognized in delayed testing than immediate testing (p < .001). 6. There was an interaction between actions and retention intervals in false memory testing (p < .05). Although false recognition of all actions increased at the longer retention, as time passed, false recognition in typical action increased more remarkably, in contrast to the increases in the other two types of actions.